2015
DOI: 10.1158/0008-5472.can-14-2377
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Promotes Regulatory T-cell Responses in Tumors by Inducing Vitamin A Metabolism in Dendritic Cells

Abstract: Tumors actively suppress antitumor immunity creating formidable barriers to successful cancer immunotherapy. The molecular mechanisms underlying tumor-induced immune tolerance are largely unknown. In the present study, we show that dendritic cells (DCs) in the tumor microenvironment (TME) acquire the ability to metabolize vitamin A to produce retinoic acid (RA), which drives T regulatory responses and immune tolerance. Tolerogenic responses were dependent on induction of vitamin A-metabolizing enzymes via the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 43 publications
3
127
0
1
Order By: Relevance
“…Previous studies have shown that wnt3a specifically activates β-catenin in DCs (3032). Consistent with these studies(3032), the wnt3a treatment of DCs from TCF reporter mice showed an increase in the reporter gene expression compared to untreated DCs (Fig. 4a).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that wnt3a specifically activates β-catenin in DCs (3032). Consistent with these studies(3032), the wnt3a treatment of DCs from TCF reporter mice showed an increase in the reporter gene expression compared to untreated DCs (Fig. 4a).…”
Section: Resultsmentioning
confidence: 94%
“…In models of gut tolerance and tumor-induced immune tolerance, our recent studies have shown that activation of β-catenin in DCs induces T regulatory responses, and suppresses intestinal inflammation and antitumor immunity (19, 32). However, whether this pathway in DCs regulates peripheral immune homeostasis and neuroinflammation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of b-catenin impairs the ability of DCs to induce Tregs (20), instead the activation of b-catenin pathway increases the capacity of DC to release IL10 and promote immune tolerance, (21,22). In DCs, b-catenin signaling synergizes with other pathways, such as the Erk pathway, to induce anti-inflammatory cytokines and proliferation of Tregs.…”
Section: Pazopanib-treated Dcs Are Able To Increase T-cell Activitymentioning
confidence: 99%
“…4 However, it is possible that tumors can induce regulatory DCs by activating b-catenin/ TCF pathway and promote immune suppression. In our recent study, 5 we have put this idea to the test and showed tumors exploit b-catenin/TCF pathway as a potential immune evasion mechanism.…”
Section: Tumor-induced Immune Tolerance Via B-catenin/retinoicmentioning
confidence: 99%
“…Consistent with these studies, our data showed that this pathway is active in DCs isolated from tumor draining lymph node (TDLN) and tumor. 5 To further examine the role of this pathway in DC-mediated immune suppression, we have generated mice that selectively lacked b-catenin in DCs (referred to as b-cat DDC mice). DCspecific deletion of b-catenin resulted in delayed melanoma (MO4) and thymoma tumor growth compared with control mice.…”
Section: Tumor-induced Immune Tolerance Via B-catenin/retinoicmentioning
confidence: 99%